Profiling Oman education data using data visualization technique - Alalawi, Sultan Juma Sultan; Mohd Shaharanee, Izwan Nizal; Jamil, Jastini (2016)
This research works presents an innovative data visualization technique to understand and visualize the information of Oman’s education data generated from the Ministry of Education Oman “Educational Portal”.The Ministry of Education in Sultanate of Oman have huge databases contains massive information.The volume of data in the database increase yearly as many students, teachers and employees enter into the database. The task for discovering and analyzing these vast volumes of data becomes increasingly difficult. Information visualization and data mining offer a better ways in dealing with large volume of information.In this paper, an innovative information visualization technique is developed to visualize the complex multidimensional educational data. Microsoft Excel Dashboard, Visual Basic Application (VBA) and Pivot Table are utilized to visualize the data.Findings from the summarization of the data are presented, and it is argued that information visualization can help related stakeholders to become aware of hidden and interesting information from large amount of data drowning in their educational portal.